Rapid-Scan Nonlinear Time-Resolved Spectroscopy over Arbitrary Delay Intervals - Tobias Flöry; Vinzenz Stummer; Justinas Pupeikis; Benjamin Willenberg; Alexander Nussbaum-Lapping; Edgar Kaksis; Franco V. A. Camargo; Martynas Barkauskas; Christopher R. Phillips; Ursula Keller; Giulio Cerullo; Audrius Pugžlys; et al. (Ultrafast Science, 2023)
Femtosecond dual-comb lasers have revolutionized linear Fourier-domain spectroscopy by offering a rapid motion-free, precise, and accurate measurement mode with easy registration of the combs beat note in the radio frequency domain. Extensions of this technique already found application for nonlinear time-resolved spectroscopy within the energy limit available from sources operating at the full oscillator repetition rate. Here, we present a technique based on time filtering of femtosecond frequency combs by pulse gating in a laser amplifier. This gives the required boost to the pulse energy and provides the flexibility to engineer pairs of arbitrarily delayed wavelength-tunable pulses for pump–probe techniques. Using a dual-channel millijoule amplifier, we demonstrate programmable generation of both extremely short, fs, and extremely long (>ns) interpulse delays. A predetermined arbitrarily chosen interpulse delay can be directly realized in each successive amplifier shot, eliminating the massive waiting time required to alter the delay setting by means of an optomechanical line or an asynchronous scan of 2 free-running oscillators. We confirm the versatility of this delay generation method by measuring χ(2) cross-correlation and χ(3) multicomponent population recovery kinetics.